Linear Quadratic Optimization for Models with Rational Expectations - Hans M. Amman; David A. Kendrick (Tinbergen Institute, 1997)
In this paper we present a method for using rational expectations in a linear-quadratic optimizationframework. Following the approach put forward by Sims, we solve the model through a QZdecomposition, which is generally easier to implement than the more widely used method of Blanchardand Kahn.
Keywords: 330; Nichtlineare Optimierung; Rationale Erwartung; Dekompositionsverfahren; Theorie